2012
DOI: 10.4103/2278-0203.99762
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in miniscrew utilization among Indian orthodontists

Abstract: Background:There is limited data about current utilization of miniscrews in orthodontic practices in India. The purpose of this survey was to obtain information on clinical utilization of miniscrews among orthodontists in India.Materials and Methods:A survey questionnaire was prepared and mailed to 2100 qualified and registered orthodontists in India.Results:A total of 1691 orthodontists responded to the survey, with a response rate of 80.52%. Among them, 952 (56.3%) had never used miniscrews in their clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 4 publications
(3 reference statements)
1
47
3
Order By: Relevance
“…The study by Meeran et al, found that while 62.65% of orthodontists used surgical guides, 37.35% did not use a guide for mini-screw placement. 20 Furthermore, 60.2% practitioners in our study indicated that they loaded mini-screws immediately after placement, which is less than that reported in another study 93.6%. 19 Loading time may differ depending on the given case.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…The study by Meeran et al, found that while 62.65% of orthodontists used surgical guides, 37.35% did not use a guide for mini-screw placement. 20 Furthermore, 60.2% practitioners in our study indicated that they loaded mini-screws immediately after placement, which is less than that reported in another study 93.6%. 19 Loading time may differ depending on the given case.…”
Section: Discussioncontrasting
confidence: 74%
“…Another study indicated that most orthodontists 54% used a combination of topical and local anesthesia. 20 In present study, there was no significant association between type of anesthesia and implant success (p >0.05). Moreover, a 70-90% success rate noted by the majority of respondents in this study was consistent with previous studies.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations